Pharmaceutical stability and prodrug studies on the antidepressant bupropion - O'Byrne, Paul Matthew (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2010)
This thesis describes the work carried out at the School of Pharmacy and Pharmaceutical Sciences, Trinity College on the pharmaceutical stability and prodrug studies on the antidepressant bupropion. Chapter 1 gives an overview of bupropion, discussing its therapeutic uses, pharmacokinetics, adverse effects and pharmacology. The prodrug concept is introduced with particular reference to central nervous system brain delivery and prodrug options relating to these types. Prodrugs of bupropion would be advantageous to improve its stability and side-effect profile. Chapter 2 addresses the aqueous stability of bupropion with particular emphasis on the kinetics of degradation. The pH rate profile of bupropion shows instability above pH 5 and this problem can be addressed by prodrug design.
Keywords: Pharmacy, Ph.D.; Ph.D. Trinity College Dublin